2013
DOI: 10.1017/s1368980013002802
|View full text |Cite
|
Sign up to set email alerts
|

Serum aflatoxin levels of the healthy adult population living in the north and south regions of Turkey

Abstract: Objective: To determine the serum concentrations of aflatoxin B 1 (AFB 1 ), aflatoxin B 2 (AFB 2 ), aflatoxin G 1 (AFG 1 ) and aflatoxin G 2 (AFG 2 ) in the healthy adult population living in both the Black Sea and Mediterranean regions of Turkey and to investigate the regional, seasonal and gender variability in aflatoxins (AF) exposure in these regions. Design: Serum AFB 1 , AFB 2 , AFG 1 and AFG 2 concentrations were analysed by HPLC. Settings: In total, four hundred and eighty-four serum samples were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The detection of AF B2, AF G1 and AFG2 subtypes, determined at low levels in food, has not been confirmed as a sensitive method in blood for exposure. There are a few studies in literature demonstrating the AF levels directly in biological samples . Corcuera et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of AF B2, AF G1 and AFG2 subtypes, determined at low levels in food, has not been confirmed as a sensitive method in blood for exposure. There are a few studies in literature demonstrating the AF levels directly in biological samples . Corcuera et al .…”
Section: Discussionmentioning
confidence: 99%
“…The detection of AF B2, AF G1 and AFG2 subtypes, determined at low levels in food, has not been confirmed as a sensitive method in blood for exposure. There are a few studies in literature demonstrating the AF levels directly in biological samples [12,23,35]. Corcuera et al [36] reported that the level of AFB 1 in plasma from rats given a single dose of 0.25 mg/ kg of AFB 1 by oral gavage was 24.8 ng/mL and 9.5 ng/ mL at 10 min and 30 min, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and 39.1 for both rural and peri-urban samples, respectively. Most of the other selected developing countries such as Brazil 42 , Kenya 43 , Ghana 44 , Egypt 45 , Malaysia 46 and Turkey 47 had lower geometric means than in Gambia; but such means were all greater than the means for both children and mothers/adults from Timor-Leste. Among the selected countries Timor-Leste only shows a geometric mean slightly greater than those of developed countries - USA (0 pg mg −1 ) and Canada (non-detectable) 48 ; and France and Poland (0 pg mg −1 ) 45 .…”
Section: Discussionmentioning
confidence: 90%
“…in children and adults/mothers blood samples in this study and selected countries.CountryChild/AdultRange of agePositive samples (%)Geo. mean Afla-alb levelBenin & Togo 37 Children9 to 60 mth9932.8Brazil 45 n/an/a6210.7Canada 48 n/an/a(nd) 0(nd) 0Egypt 45 Adult (male/female36 to 74 yrs675France & Poland 45 n/an/a0/74 (0)0Ghana 44 Adult/mother14 to 48 yrs405Guinea 40 Children2 to 5 yrs969.9Kenya 43 Pregnant/with child >24 mthn/an/a7.5Malaysia 46 Adult male/female18 to 85 yrs974.5Tanzania 38 Children12 to 22 mth8412.9The Gambia 3,39,41 Adult (male/female) Rural<15 to >35 yrs10061.8Mothern/a10040.4Adult (male/female) Peri urban<15 to >35 yrs98.839.1Children1.4 yrs1110.1Timor-LesteAdult (non-pregnant)14 to 60 yrs810.98Children6 to 59 mth830.64Turkey 47 Adult (male/female)17 to 64861.1USA 48 n/an/a1.20.3n/a, non-available; nd, non-detectable.…”
Section: Discussionmentioning
confidence: 99%